Technology transfer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The workshops of the Union for Appropriate Technology Assistance (UNATA) in Belgium are currently involved in their first technology transfer operation. The earth brick presses that were developed by UNATA will now be manufactured in Cameroon by...